3D segmentation of intervertebral discs: from concept to the fabrication of patient-specific scaffolds. Issue 2 (April 2017) - Oner, T; Cengiz, IF; Pitikakis, M; Cesario, L; Parascandolo, P; Vosilla, L; Viano, G; Oliveira, JM; Reis, RL; Silva-Correia, J
Aim: To develop a methodology for producing patient-specific scaffolds that mimic the annulus fibrosus (AF) of the human intervertebral disc by means of combining MRI and 3D bioprinting.Methods: In order to obtain the AF 3D model from patient's volumetric MRI dataset, the RheumaSCORE segmentation software was used. Polycaprolactone scaffolds with three different internal architectures were fabricated by 3D bioprinting, and characterized by microcomputed tomography.Results: The demonstrated methodology of a geometry reconstruction pipeline enabled us to successfully obtain an accurate AF model and 3D print patient-specific scaffolds with different internal architectures.Conclusion: The results guide us toward patient-specific intervertebral disc tissue engineering as demonstrated by a way of manufacturing personalized scaffolds using patient's MRI data.